Evaluating Non-Composted Red Cotton Tree (Bombax ceiba) Sawdust Mixtures for Raising Okra (Abelmoschus esculentus (L.) Moench) in Pots - Muhammad Yasin; Farhan Anwar; Hassan Noorani; Sher Muhammad; Athar Mahmood; Talha Javed; Baber Ali; Khadiga Alharbi; Ibrahim A. Saleh; Hashem A. Abu-Harirah (Agronomy, 2022)
In modern agriculture, the substrate industry prefers porous materials for plants to provide water and nutrients in soilless cultivation. Composted sawdust is such a substrate. The sawdust industry is interested in avoiding composting sawdust because it is time and labor-consuming. The study objective was to evaluate whether non-composted (fresh) Bombax ceiba (red cotton tree) sawdust with added nutrients could be an alternative to composted sawdust for okra production. The sawdust was mixed with nutrients in the form of banana peels (a potassium source), eggshells (a calcium source), and urea (a nitrogen source). We conducted two independent pot experiments. Treatments were viz.: T1: non-fertilized 100% sandy clay loam soil (control) (vol/vol); T2: non-composted 100% B. ceiba sawdust (vol/vol); T3: non-composted 80% B. ceiba sawdust + 20% banana peels (vol/vol); T4: non-composted 60% B. ceiba sawdust + 20% banana peels + 20% eggshells (vol/vol); T5: non-composted 60% B. ceiba sawdust + 20% banana peels + 20% eggshells (vol/vol) + urea (@ 91 kg N ha−1). In both experiments, the germination of okra seeds was unaffected by the sawdust mixtures. The phenological development of okra was significantly greater in non-fertilized clay loam soil than in any non-composted sawdust mixtures. Plant height, leaf relative water content, stability index of the membrane, root length, chlorophyll content index, root and shoot dry and fresh weight, stem diameter, and single leaf area of okra were lower in all non-composted B. ceiba sawdust mixtures compared to the control. In contrast to T2, T5 resulted in fewer days before the first flower developed, an increase in the number of pods plant−1, length of pod plant−1, the diameter of the pod, fresh and dry weight of pod plant−1, and the seed numbers pod−1. It is concluded that amending non-composted B. ceiba sawdust with banana peels, eggshells, and urea (T5) enhanced its perspective as a growth medium for okra. Nonetheless, the amendments were unlikely to establish an adequate yield of okra, as was the case with non-fertilized sandy clay loam soil.